Analysis of Lifestyle and Consumer Attitude Towards Intention to Purchase a Personal Car During Pandemic - MARINA, DIANA; Pandjaitan, Nurmala K; Hasanah, Nur; Cesna, Galih Putra (Pandawan, 2023)
The COVID-19 pandemic is a new virus that allegedly originated in Wuhan, China, in 2019. This COVID-19 has spread rapidly, disrupting all sectors of life in various countries. The Covid-19 pandemic also impacted Indonesia's economic decline in 2020 and triggered the acceleration of the world recession. The policy of Large-Scale Social Restrictions (PSBB) and regional quarantine significantly impacted the delay in the distribution of goods, which resulted in employee housing and even layoffs. The fear of contracting COVID-19 triggers the intensity of the use of private vehicles as well as the intention to own a car. Lifestyle changes in traveling, especially the choice of the private car, are also influenced by the primary destination and distance traveled during the pandemic. But the economic pressure of the impact of the pandemic has become a substantial perception control that holds back the realization of intention to make a personal vehicle purchase decision. Although there has been an increase in the frequency of private vehicle use during the pandemic, in reality, the increase has not impacted private car sales. This is caused by the purchasing power of consumers, who are still hampered because of the pandemic. The government itself is aware that the automotive industry is an industry that has a significant contribution to 20 percent of the national Gross Domestic Product (GDP) and absorbs 1.5 million workers. This prompted the government to issue a stimulus in the form of policy relaxation to boost the productivity of the auto industry.